Application of ultrasonic physics in material technology - MAŁECKI, Ignacy (Archives of Acoustics, 2016)
Measurements of the velocity and attenuation of ultrasonic wave as the basis of the inspection of technological processes. Ultrasonic defectoscopy as used for the detection of internal defects and measurement errors. Correlation between indications of a defectoscope and the mechanical strength of the construction. Determination of elasticity constants of materials. The effect of material grain size upon the attenuation of ultrasonic waves. Stress action vs. increased attenuation. Continuous inspection of the processes: burning of ceramics, polimerization, metal solidification. The effect of microstructure upon the propagation of ultrasonic waves. Properties of materials at low temperatures.